Application of Energy-Concentrated Hydraulic Blasting Technology in Tunnel Construction in China - Feng Han; Jigang Li; Yuancheng Cai; Qiang Wang; Junling Qiu (Shock and Vibration)
The construction of traffic network brings opportunities to the development of tunnel construction technology. At present, the construction of rock tunnels is still dominated by drilling and blasting. There are some problems in conventional blasting, such as over and underexcavation, damage of surrounding rock, large blasting vibration, and high content of tunnel dust. The energy-concentrated hydraulic blasting technology (ECHBT) combines the advantages of energy-concentrated blasting technology (ECBT) and hydraulic blasting technology (HBT) and makes up for the defects of conventional blasting. This paper summarizes the principle of ECHBT and its application effect in tunnel construction in China. In addition to solving the problems existing in conventional blasting technology, ECHBT can also improve tunneling efficiency, can be used in special stratum tunnels, and can save construction costs. However, there are also some factors affecting the blasting effect in practical applications, which need to be paid attention to. At present, there is little theoretical research on ECHBT; with the further improvement of optimization research, it can be expected to be more widely used in the field of tunnel construction.